2003
DOI: 10.4315/0362-028x-66.7.1227
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Cooking, Cooling, and Subsequent Refrigeration on the Growth or Survival of Clostridium perfringens in Cooked Meat and Poultry Products

Abstract: In January 1999, the Food Safety and Inspection Service (FSIS) finalized performance standards for the cooking and chilling of meat and poultry products in federally inspected establishments. More restrictive chilling (stabilization) requirements were adopted despite the lack of strong evidence of a public health risk posed by industry practices employing the original May 1988 guidelines (U.S. Department of Agriculture FSIS Directive 7110.3). Baseline data led the FSIS to estimate a "worst case" of 10(4) Clost… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
24
0
1

Year Published

2004
2004
2016
2016

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(26 citation statements)
references
References 20 publications
1
24
0
1
Order By: Relevance
“…Our results also show good agreement with those of Kalinowski et al (14), who demonstrated a net growth of more than 2 log 10 CFU/g was observed during cooling uncured turkey samples from 48.9 to 12.8°C over 6 h, which is a rate approximately equivalent to the 12-h cooling process shown in Table 1. Again, the Juneja 1999 model underpredicts the growth observed by Kalinowski et al…”
Section: Discussionsupporting
confidence: 82%
“…Our results also show good agreement with those of Kalinowski et al (14), who demonstrated a net growth of more than 2 log 10 CFU/g was observed during cooling uncured turkey samples from 48.9 to 12.8°C over 6 h, which is a rate approximately equivalent to the 12-h cooling process shown in Table 1. Again, the Juneja 1999 model underpredicts the growth observed by Kalinowski et al…”
Section: Discussionsupporting
confidence: 82%
“…Furthermore, the vans used for food transport had no refrigeration and these events took place in July. The evidence of insufficient hygiene, cooling and reheating at the catering company during transport and at both venues (according to environmental health department inspections) are in keeping with a toxin-related gastroenteritis outbreak, including C. perfringens enterotoxin [4,9,10]. As the distance from the caterer to venue B was substantially longer than to venue A, the lack of adequate temperature control during transport may have led to a higher infective dose in venue B, which could explain the shorter incubation time and higher proportion of cases with vomiting.…”
Section: Discussionmentioning
confidence: 99%
“…Several challenge studies have been conducted under laboratory conditions to investigate growth of C. perfringens during cooling of cooked meat products (20,31). However, the cooking conditions in these studies were not representative of the cooking processes used in commercial establishments.…”
mentioning
confidence: 99%